Gender and sexuality of people with mental disorders in Brazil - Jaqueline Almeida Guimarães Barbosa; Alain Giami; Maria Imaculada de Fátima Freitas
The goal of this study was to understand the ways of living and thinking about sexuality of people with mental disorders. Open interviews were conducted with men and women in public mental health services in Brazil. Transcrips were examined based on the proposal of sexual scripts. Major imbalances coming from conceptions of masculinity and femininity in society were identified in the sexual scripts experienced by these men and women. Interviewees have little pleasure in their sexual lives, with recurrent complaints of sexual abuse, even by steady partners; prejudice; and lack of affection in their relationships. Additionally, they were found to have few self-care skills concerning sexual health, in a context marked by social exclusion. The results showed the need to promote sexual health as a human right, and fight gender stereotypes, which cause so much damage to the sexual health of people with mental disorders.